Utilization of Shoot Cuttings for Elimination of PLRV and PVY by Thermotherapy and Chemotherapy from Potato (Solanum tuberosum L.) - Dhital, S. P.; Sakha, B. M.; Lim, H. T. (Nepal Journal of Science and Technology, 2007)
Heat and ribavirin treatments were applied for the elimination of potato leaf roll virus (PLRV) and potato virus Y (PVY) from the potato genotype F 9-99. The explants, rooted young plantlets, cultured on MS medium with and without ribavirin (20 mg l-1) were subjected to thermotherapy (35ºC/31ºC, 4 h alternating periods) and room temperature (25ºC) for 30 days. Double antibody sandwich - enzyme linked immunosorbent assay (DAS-ELISA) testing following the therapies revealed that ribavirin alone was enable to eliminate 10% each of PLRV and PVY, whereas along with thermotherapy its efficacy increased to 25% PLRV and 20% PVY elimination. In another experiment, three potato genotypes F 9-99 infected with PLRV and PVY, Gui Valley with PLRV infection and Rose Valley with PVY infection were evaluated. Ribavirin (20 mg l-1) and ASA (acetylsalicylic acid) (10-5 M) were supplemented in liquid culture medium alone or in combination with thermotherapy for three successive cycles of 30-36 days interval. Heat and/or ribavirin suppressed survival and plant height whereas ASA promoted the survival as well as plant height even under heat treatment. After each cycle, the effect of treatment on virus elimination was evaluated by DAS-ELISA. The combined application of ribavirin and ASA with thermotherapy after three cycles of treatment showed up to 47.4% PLRV and 57.9% PVY elimination in F 9-99. In the case of single viral infection of PLRV or PVY the same combined treatment showed up to 58.8% PLRV and 61.1% PVY free plantlets. Virus elimination was also confirmed by transplanting in vitro grown plantlets in a net house and then retesting after 45 days of in vivo growth. This novel technique would be highly efficient for virus elimination within a short duration in diverse genotypes of potato. Nepal Journal of Science and Technology 7 2006